2021
DOI: 10.3390/molecules26113204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Composition of Lyophilisates Obtained from Aloe arborescens Gel of Leaves of Different Ages from Controlled Crops

Abstract: The aim of the study is to evaluate the composition of lyophilisates obtained from Aloe arborescens leaf gel at the age of one to four years. The leaves were obtained from controlled crops, which allowed to exclude environmental factors as variables. It was confirmed that the lyophilisates obtained from different years of Aloe arborescens leaf gel varied in chromatographic analyses in terms of aloin A and aloenin A content (high-performance liquid chromatography with diode-array detection HPLC-DAD, high-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…This research is a continuation of our previous studies, which included the analysis of the content of aloin A, aloenin A, polyphenolic compounds, and phenolic acids in raw material, and the evaluation of the antioxidant activity of extracts from the freeze-dried leaf pulp of A. arborescens from 1-, 2-, 3- and 4-year-old plants. The effects of the study mentioned above can be found in one of our published papers [ 23 ]. This manuscript presents the results of our research on the lyophilizate from 3-year-old plants, which turned out to exhibit a higher activity and height content of active compounds ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This research is a continuation of our previous studies, which included the analysis of the content of aloin A, aloenin A, polyphenolic compounds, and phenolic acids in raw material, and the evaluation of the antioxidant activity of extracts from the freeze-dried leaf pulp of A. arborescens from 1-, 2-, 3- and 4-year-old plants. The effects of the study mentioned above can be found in one of our published papers [ 23 ]. This manuscript presents the results of our research on the lyophilizate from 3-year-old plants, which turned out to exhibit a higher activity and height content of active compounds ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research on the plant material Aloe arborescens showed that the lyophilisates obtained from the pulp of 3-year-old leaves contain the highest polyphenol content, which translates into the highest antioxidant activity against the DPPH radical [ 23 ]. Bearing in mind the results obtained earlier, we focused on assessing the safety and activity potential of lyophilisates from 3-year-old Aloe arborescens leaves in the current research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of main active compounds (aloin A and aloenin A) were determined by using the HPLC-Diode-Array Detection method (equipment LC system, Dionex Thermoline Fisher Scientific) with Chromeleon software version 7.0) described previously [ 20 ]. Briefly, separations were performed on a LiChrospher RP-18 column, 5 μm particle size, 250 mm × 4 mm LiChroCART ® 250-4 (Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In the first phase of the research, we compared the composition of leaves obtained from one, two, three and four-year-old plants. Leaves obtained from three-year-old plants were indicated as the most worthwhile as they had the highest total phenolic concentration and total antioxidant activity [ 20 ]. For them, ethanol extracts were obtained, for which the safety of their use and effectiveness in relation to fibroblasts was also proven [ 21 ].…”
Section: Introductionmentioning
confidence: 99%